2021
DOI: 10.3390/jcm10122546
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Meniscus Repair with or without Multiple Intra-Articular Injections of Platelet Rich Plasma after Surgery

Abstract: Preservation of the meniscal volume is crucial in meniscus repair. The goal of this study was to evaluate the clinical outcome of repeated intra-articular platelet-rich plasma (PRP) injections after arthroscopic repair of a traumatic meniscal tear. We retrospectively reviewed 61 primary meniscal repairs in 61 patients (PRP group: 30; non-PRP: 31) from 2017 to 2018. Patients in the PRP group received repeated intra-articular PRP injections in week 2,4,6 after the primary meniscus repair. Subsequent meniscal rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…After removing 88 duplicate studies, a total of 116 records were excluded because they were deemed irrelevant according to the title and abstract. After thoroughly reviewing the full texts of the 16 potentially eligible articles, nine articles (two RCTs and seven non-RCTs) were selected for the final analysis, which were published between 2015 and 2021 [ 19 , 20 , 25 , 26 , 30 34 ]. A flowchart depicting the study selection strategy is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After removing 88 duplicate studies, a total of 116 records were excluded because they were deemed irrelevant according to the title and abstract. After thoroughly reviewing the full texts of the 16 potentially eligible articles, nine articles (two RCTs and seven non-RCTs) were selected for the final analysis, which were published between 2015 and 2021 [ 19 , 20 , 25 , 26 , 30 34 ]. A flowchart depicting the study selection strategy is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We identified six studies in which PRP was delivered arthroscopically and sutured or injected into the repair site [ 19 , 20 , 25 , 31 33 ], one study with in situ PRP injection into the repaired lesion after mini-arthrotomy [ 30 ], one study with multiple intra-articular PRP injections after meniscus repair surgery [ 26 ], and one study with minimally invasive (percutaneous) intrameniscal PRP application [ 34 ]. Furthermore, there were seven studies using LR-PRP, with two other studies not specifying LR versus LP formulations [ 20 , 26 ]. Two studies utilized PRP with a fibrin matrix [ 20 ] or clot [ 32 ] that was inserted into the repair site.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations